The Influence of Compensation, Work Environment, and Motivation on Teacher Performance in the Nurul Ulum Ngampon Foundation - Andini Mirnayanti; Moh. Muklis Sulaeman; Diah Ayu Novitasari; Nurus Safa'atillah (RTTM, 2024)
This study aims to analyze and understand the influence of compensation, work environment, and motivation on teacher performance at the Nurul Ulum Ngampon Foundation. The quality of education is highly dependent on teacher performance as the spearhead in the learning process. Teacher performance is influenced by various complex factors, including the welfare received, work environment conditions, and the level of internal and external motivation possessed. This study uses a quantitative approach with a survey method, which involves the active participation of teachers at the Nurul Ulum Ngampon Foundation. The collected data were then analyzed using multiple linear regression techniques with the help of SPSS statistical software. This analysis aims to identify the relationship between the independent variables (compensation, work environment, and motivation) with the dependent variable (teacher performance). The results of this study are expected to provide valuable recommendations for the foundation in an effort to improve teacher welfare, create a more conducive work environment, and increase work motivation. Thus, it is hoped that teacher performance can be significantly improved, which will ultimately contribute to the achievement of better educational goals at the Nurul Ulum Ngampon Foundation. This study is also expected to be a reference for further research in the field of human resource management, especially related to the factors that influence teacher performance.